Pelaksanaan Pengadaan Tanah Bagi Pembangunan Untuk Kepentingan Umum - Sumiati, Lilik; Rahman, Arief (Private Law, 2024)
This study aims to determine the procedures for implementing land acquisition for constructing the Lombok International Airport ByPass road to the Land Acquisition Area for constructing the Lombok International Airport ByPass road to the Mandalika Special Economic Zone. This study uses empirical legal research with the statutory, conceptual, and sociological approaches. The data types in this study are primary and secondary, while the data sources use library research and field research. Techniques and ways of obtaining data are by conducting interviews and observations. The purpose of this study is to find out the procedures for implementing land acquisition for the construction of the Lombok International Airport ByPass road to the Mandalika Special Economic Zone, and to find out the inhibiting factors in this activity. The procedure for implementing land acquisition for the construction of the Lombok International Airport By Pass to the Mandalika Special Economic Zone as stipulated in Law Number 11 of 2020 Ciptaker regulates 4 (four) stages of acquisition starting from planning, preparation, implementation, and delivery of results. The land acquisition implementation committee has carried out land acquisition procedures following the provisions of the Laws and Regulations. The obstacles in constructing the Lombok International Airport By Pass road to the Mandalik Special Economic Zone include social, cultural, and economic factors.